Kita Masih Murji’ah: Mencari Akar Teologis Pemahaman Keagamaan Umat Islam di Indonesia - Fauzan Saleh (TSAQAFAH, 2011)
Generally speaking, Muslims’ life, be it in socio-cultural, political, or economicaspects, is determined by one’s theological insight. Probably, it might not be fullyrealized, since the theological outlook is by nature latent, being integrated intoone’s inner life. However, it has a considerable contribution to constructing one’sweltanschauung. It is true that theology is the knowledge about God. Yet, humanunderstanding about God, who He is, and how human should establish his orher relationship with Him, will disclose the veracity of human behavior and conduct.Theology, being not so far different from philosophy, may play an instrumentalrole in the shaping of one’s principle of life. Up to now, one of the most influentialtheological doctrines in Islam is the one formulated by the Murji’ites. Thistheological school of thought emerged in the same period as some othercontemporaneous sects, the Kharijite, and the Mu’tazilite..Today, these theologicalschools have in effect disappeared, and thus they are not recognized any longer.Nevertheless, some elements of Murji’ite doctrines remain influential, beingintegrated into the currently surviving Islamic theological school, the Sunnite.Characteristically, the Murji’ite tends to be permissive, less decisive, and is allowingthe moral problems that occur in human life to be solved by God alone, not byhuman. It is believed that only God can judge.